Faktor-Faktor Yang Mempengaruhi Perilaku Ibu Terhadap Ketepatan Kunjungan Antenatal Care Di RSU Bahagia Makassar - Sri Resky Mustafa; Nur Ismi Wahyuni (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: to identify  the factors associated with the accuracy of ANC visitsMethods:  The type of research used in this study is a quantitative survey method with a Cross Sectional approach that uses a total sampling technique of 37 respondents. Data was collected using a questionnaire. The test used was chi-square with a significance level of = 0.05. This research was conducted at the Bahagia Makassar General Hospital for 2 weeks.Results:  There was no relationship between mother's knowledge and the accuracy of ANC visits (p0.63), but there was a relationship with mother's attitude (p=0.01), husband's support (p=0.05) at Happy Hospital Makassar.Conclusion:  The results of this study can increase knowledge and awareness for pregnant women about the importance of antenatal care for mothers and their unborn babies.